Developing a Community-Based Exercise and Physical Programme for Runners With Patellofemoral Pain in Under-Resourced Communities: A Delphi Study. - Kunene, Siyabonga (Physiotherapy Canada, 2025)
Purpose: Patellofemoral pain (PFP) is a multifactorial condition that is highly prevalent among recreational runners. Poor homeostasis between load and runner's capacity is the main cause of PFP. A low-cost and community-based intervention is needed to address the rehabilitation needs of runners in under-resourced communities. The purpose of this study was to develop a community-based exercise and physical programme for runners with PFP in under-resourced communities. Method: This study used a Delphi method that included sports experts (physicians, physiotherapists, biokineticists, podiatrists, and sports therapists) who consented to participate. Delphi included three rounds of iterations to attain consensus among experts. Experts reached a consensus by rating PFP programme items using the 5-point Likert scale. Results: Ten experts participated. There were more males (n = 6) than females (n = 4). Participants were aged between 36 and 55 years (n = 5) and had 16–20 years of clinical experience (n = 5). Delphi process yielded an exercise and physical intervention, which included the following 10 recommended strategies: hip muscle training, quadriceps muscle training, general lower limb and trunk strengthening, use of appropriate running shoes, and use of prefabricated in-shoe foot orthosis, tissue mobilization, patellar taping/bracing, education, flexibility exercises, addressing external loads, and addressing non-physical internal loads. Conclusions: A consensus was reached for a suitable exercise and physical programme for runners in under-resourced communities. A follow-up implementation study is, therefore, recommended.